A experimental study of a cable-pulleys spring-damper energy dissipation system for buildings. (1st July 2022) - Hernández, Francisco; Astroza, Rodrigo; Beltrán, Juan Felipe; Zhang, Xihong; Mercado, Vicente
Abstract: An energy dissipation mechanism made of a cable-pulleys system placed in series with a spring-damper device (fluid viscous) is experimentally studied. The system aims to provide high damping ratios for all the structural modes by using a unique spring-damper device to dissipate the seismic energy of the entire structure (and all its structural modes). Shake table tests and pull-back tests are carried out on a scaled five-story structure to compare the dissipation capabilities provided by the proposed system. Therefore, the same structure is tested under different configurations that included: i) the structure itself without any energy mitigation device, ii) the structure with viscous dampers installed on each story, iii) the structure with the proposed cable-pulleys and the spring-damper system, and iv) the structure with the cable-pulleys system but without any dissipation device. The experimental results showed that the structure with the proposed system exhibits a highly nonlinear response (mainly explained by the cable-pulleys interaction) evidenced by the significant change of the structure's dynamic properties during the time. The Short-Time Transfer Function plots show that the structure's natural frequencies change significantly when the cable-pulleys system is included. Complementarily, a novel time-variant system identification approach, termed Mod-ζ(var), is proposed, which allows estimating the time-variant evolution of the structure's dynamic properties during seismic tests (natural frequencies, damping ratios, and mode shapes). Moreover, the Mod-ζ(var) approach also enables computing relevant engineering quantities such as the empirical response spectrum from experimental data. It is found that the analyzed energy dissipation system provides high damping ratios (>10%) for all the structural modes, allowing reducing the seismic demands in terms of the empirical response spectrum, inter-story drifts, inter-story shear forces, peak accelerations, and Housner Intensities at each floor.